Linguistic representation of English vocabulary attrition - Yu, Zhonggen; Chan, Swee Heng; Abdullah, Ain Nadzimah (Universiti Putra Malaysia Press, 2011)
This study aimed to identify vocabulary attrition and the linguistic representation of English vocabulary attrition. One hundred and twenty-one participants were randomly selected to participate in the vocabulary tests. The results of vocabulary attrition tests were measured through non-parametric 2-related samples tests and linguistic analyses in terms of phonology, morphology, and semantics. The authors identified a statistically significant vocabulary attrition during a two-month holiday. In the field of phonology, the authors reached the conclusion that medial segments of words are easily attrited, while words with similar onsets are easily attrited and the words with similar general rhythms are easily attrited. Furthermore, in the morphological area, it was argued that suffixes are subject to attrition, while words with similar onsets and general rhythms are easily attrited. As far as semantic representation of lexical attrition is concerned, the authors purport that the participants tend to mix synonyms, antonyms, and the words coordinately associated, superordinately related, or affectively connected. The affective factors, including active, passive and associative imagination, may cause lexical attrition as well.